Intellectual and artistic review of “My Prophet SAWW”: ’’میرے حضورﷺ‘‘کا فکری و فنّی جائزہ - Saqib, Abbas Ali Shah; Hanif, Fozia; Jafar, Muhammad (Al Khadim Research Journal of Islamic Culture and Civilization, 2023)
Syed Wajeeh-u-Seema Irfani is a renowned poet of Rawalpindi. He has a splendid and unique naatiya consciousness. His favourite field is naat. In his naat he describes the different aspects of the Seert e Rasool (SAWW) the qualities and the nobility. This article will present thematic dimensions, consideration and sagacity of his poetry.